Data Library Maintenance and Maproom Development Training with Zambia Meteorology Department - Rose, Alison (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Maprooms are powerful and freely accessible online visuals of climate data tailored to the agricultural and other sectors, play a large role in making climate information more accessible and usable. By translating past, present, or future conditions into expected impacts and management advisories, they are meeting the needs of different decision-makers for location- and sector-specific information for adaptation in Africa.